The pelagic food web of the Western Adriatic Sea: a focus on the role of small pelagics - E. Fanelli; Z. Da Ros; S. Menicucci; S. Malavolti; I. Biagiotti; G. Canduci; A. De Felice; I. Leonori (Scientific Reports, 2023)
Abstract The Adriatic Sea is one of the largest areas of occurrence of shared small pelagic stocks and the most fished area of the Mediterranean Sea, which is in turn one of the most exploited basins of the world. The variations in the stable isotope contents (δ 15N and δ 13C) were determined for three small pelagic fishes (i.e., Engraulis encrasicolus, Sardina pilchardus, and Sprattus sprattus, respectively known as anchovies, sardines and sprats) collected across the western side of the basin. Our data allowed to determine the width and features of their trophic niches, to assess potential overlap or resource partitioning among them, and likely anticipate species adaptation to future climate change scenarios. Moreover, variations in stable isotope contents were correlated to both resource availability (i.e., mesozooplankton) and environmental variables. The high productivity and in turn the high resource availability of the basin, especially in the northern part, resulted in favor of the resource partitioning that occurs in each sub-area of the Adriatic Sea among the three species. Medium-sized specimens of the three species mostly fed on small zooplankton, while adult sprats relied on large copepods and those of sardines and anchovies also consumed large portion of phytoplankton, confirming the high trophic plasticity of these two dominants small pelagic species. However, considering that anchovies have the greatest degree of trophic diversity compared with the other two species, they could be the most adapted to changing feeding conditions. The increase in sea temperatures that are reducing primary production and in turn zooplankton abundances, coupled with even more frequent extreme meteorologic events could exacerbate the competition for trophic resources among pelagic mesopredators, and could lead to more notable stocks’ fluctuations and unpredictable wasp-waist effects.